INTERCROPPING OF EGGPLANT AND TOMATO AS FUNCTION OF TIMES OF TRANSPLANT AND CROPPING SEASON - Cecílio Filho, Arthur Bernardes [UNESP]; Alves, Anarlete Ursulino; Galati, Vanessa Cury; Bezerra Neto, Francisco; Barbosa, José Carlos [UNESP]; Machado, Beliza Queiroz Vieira [UNESP] (FapUNIFESP (SciELO), 2022)
The use of intercropping system allows crops to better utilize inputs supplied and the productive capacity of the area, which can be advantageous to the farmer. Thus, the aim of this study was to evaluate the production performance of eggplant and industrial tomato intercropped as a function of the date of eggplant transplantation compared with tomato transplantation, in two seasons. Ten dates of eggplant transplantation were evaluated (-30,-25,-20,-15,-10,-5, 0, + 5, +10 and +15 days compared with tomato transplantation), with the first season from February to September 2009 and the second from August 2009 to February 2010. The number of commercial fruits per plant, commercial yield per plant and commercial yield of eggplant and tomato were influenced by the date of transplanting of eggplant. Highest eggplant yields were obtained in the second season, due to the more favorable weather conditions for the development of this crop. Late eggplant transplants resulted in yield losses due to tomato interference. For tomatoes, the later the eggplant was transplanted, the higher the yield. Therefore, it is concluded that the species have a high degree of interference with each other and the variation in the time of eggplant transplantation influenced the production characters of both crops. In terms of production, the intercropping of these species may not be economically viable for the farmer due to negative influences on the growth, development and production of these crops.
CONSÓRCIO DE BERINJELEIRA E TOMATEIRO EM FUNÇÃO DA DATA DE TRANSPLANTIO E ÉPOCA DE CULTIVO
Keywords: Commercial Yield; Cropping systems; Solanum lycopersicum; Solanum melongena